On the Wiener and Harary index of splitting graphs - Egan, Ma. Christine G. (Animo Repository, 2022)
Let G=(V,E) be a simple undirected graph and S⊆V. The S-splitting Graph of G denoted by Γ(G,S)=Γ is obtained by replicating the vertices x in S as well as the edges adjacent to it. In this study, we investigate the Wiener and Harary indices of an S-splitting graph of a graph G for some S⊆V(G).